Efeito de vizinhança entre macrófitas aquáticas nativa e não nativa e a influência sobre a biomassa perifítica. - Carapunarla, Luciana (2019)
The neighborhood effect may affect the production of allelopathic compounds by plants, which is a benefit in the process of biological invasion. Freshwater environments are most threatened by biological invasions and aquatic macrophytes are prominent among invasive organisms. Macrophytes together with the periphyton, are important producers in the aquatic systems, they have importance in the cycling of nutrients and energy for the next trophic levels. Was performed an experiment to test the neighborhood effect between Egeria najas Planch (native) and Hydrilla verticillata (L.f) Royle (non-native), was analyzed the productivity according to the concentration of chlorophyll-a, total dry weight (PST), and ash-free dry weight (PSLC), also calculating autotrophic index and ash percentage. Results indicated a neighborhood effect, since native species invested in defense (higher polyphenolic production) while non-natives invested in growth (higher relative biomass). Concerning to the periphyton, PST and PSLC differed between the first and the last days of the experiment. Differentially from the discussed in the recent literature, that allelopathy is not the primary mechanism used by H. verticillata during the invasion process, but resource allocation. Indeed, the production of allelopathic compounds by natives is a factor against the invasion by non-native, but it can also affect the productivity of the organic portion of the periphytic matrix. In addition, was observed that the mechanism that benefits the invasion of the non-native species, contrary to the literature, is not allelopathy, but the allocation of resources for growth and dispersal.